ANALISIS RASIO KEUANGAN KABUPATEN BERAU TAHUN 2020-2024 - Desi Indra Lestari; Dino Andriano; Meyli Yunita Aurelia; Rizki Oktaviani (Universitas Cenderawasih, 2026)
Abstract This study aims to analyze the financial performance of the Berau Regency Government based on APBD data from 2020 to 2024 by employing five financial ratios: regional independence ratio, regional financial efficiency ratio, degree of decentralization ratio, regional dependency ratio, and regional tax effectiveness ratio. The research method used is descriptive quantitative with secondary data obtained from the APBD Realization Report. The findings reveal that the average regional independence ratio is only 13%, classified as low, while the financial efficiency ratio is consistently above 100%, indicating inefficiency. The degree of decentralization ratio averages 9%, categorized as very low, whereas the regional dependency ratio averages 75.5%, showing a very high reliance on central government transfers. On the other hand, the tax effectiveness ratio varies, with an average of 92%, categorized as effective, although it declined significantly in the final year. Overall, the financial performance of Berau Regency has not been fully optimal, highlighting the need for strategies to increase local revenue and improve expenditure efficiency in order to reduce dependency on central government transfers. Keywords: Financial Performance, APBD, Berau Regency, Financial Ratios